INHIBITION MECHANISM OF COMPONENT EXTRACT OF BAWANG DAYAK ON DIABETES VIA MOLECULAR DOCKING STUDY - Ariefin, Mokhamat; Kalalinggi, Septaria Yolan (UIN Mataram, 2023)
Several compounds found within Bawang Dayak, including eleutherine and eleutherol, hold promise as potential therapeutic agentsThis research involved molecular docking and Lipinski rule analysis of 13 ligands derived from flavonoids extracted from bawang dayak. The control ligand, acarbose, was found to form four hydrogen bonds with key amino acids (Gln279, Lys156, Asp242, and Glu411), resulting in a binding energy of -9.8 kcal mol-1. Among the ligands, Ligand 3 displayed a lower binding energy of -9.9 kcal mol-1 compared to acarbose and satisfied all five criteria of Lipinski's rule, despite not forming hydrogen bonds. Instead, Ligand 3 exhibited similar hydrophobic interactions as acarbose with amino acids such as Tyr158, Phe178, Val216, Ser240, Asp242, Glu277, Gln279, His280, Arg315, Asp352, Glu411, and Arg442. Several other ligands exhibited binding energies slightly higher than acarbose, such as Ligands 4, 5, and 8, with binding energies of -8.5 kcal mol-1, -8.6 kcal mol-1, and -8.6 kcal mol-1, respectively. Based on this study, Ligands 3, 4, 5, and 8 are considered potential candidates for anti-diabetic agents. These ligands demonstrated binding energies comparable to acarbose, met at least three of the five Lipinski rule criteria, and exhibited similar amino acid interactions with acarbose, indicating their potential effectiveness in managing diabetes.